Tensões e distensões: a poética agônica de Murilo Mendes - Wesley Thales de Almeida Rocha (2018)
This dissertation develops Murilo Mendes poetry study, in first books (from Poems [1930] to Metamorphoses [1945]), highlighting the way in which the agonist's sense (the sense of tension and disarticulation) is expressed. Starting from the notion of agôn, which in the extension of its meanings, it can mean both "strife," "confrontation," "dissension," as well as "affliction," "anguish," "atonement," we will analyze how the tearing of human experience and aesthetics constitutes the primordial foundation of this poetics. The subject of poems is always shown in a dilemma: "tortured" by longings and commitments that do not adjust themselves and lead to despair, to agony. A corresponding formal process, based on the tension between opposites, expresses such conflict experiences: distinct and opposing perspectives are confronted, confusing the references of the poem and the formal elements that constitute it. Among the effects of these constants there are the disorder, the irregularity and the discontinuity stand out on the formal plane; and, on the plane of the senses, there are the contradiction and the ambivalence. These aspects have been pointed out by critics of the poet, however, under perspectives that, in our view, lead to fundamental incomprehension: on the one hand, they are treated as indices of a formal neglect on the part of the poet, with his creative practice far from notions such as balance, harmony, unity; on the other hand, the senses and effects of this sense of tension and disorder are supplanted as a way to affirm that the poet attains unity and harmony by promoting, through language, the "conciliation of opposites". As we have thought, permanent tension is the foundation of Murilo's poetics in his first books, and the aspects related to it provide expression to the tearing that placates the poet in his relation to the world, to himself, to the other and to his own poetry. The many directions, voices, perspectives that shuffle in the matrix of the poem relate to the disordered experience, the "disjointed souls of the subject," the "disjointed bodies" of the collective.